2004
DOI: 10.1892/0891-6640(2004)18<75:hawclc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity Associated with CCNU (Lomustine) Chemotherapy in Dogs

Abstract: One hundred seventy-nine tumor-bearing dogs were treated with 1-(2-chloroethyl)-3-cyclohexyl-1-nitrosourea (CCNU) between 1995 and 2001. CCNU was given as a single dose of 50-110 mg/m2 body surface area PO. Treatment interval varied, but the minimal interval between CCNU doses was 3 weeks. After treatment, 11 dogs (6.1%) developed hepatic toxicity. The median number of CCNU doses and the median total cumulative CCNU dose were significantly higher in dogs that developed hepatic toxicity (4 doses; 350 mg/m2) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 20 publications
5
37
0
Order By: Relevance
“…Hepatotoxicity associated with lomustine chemotherapy was reported in a previous study by Kristal et al 23 Although none of the dogs in the present study developed definitive evidence of overt liver failure, there was a significant trend toward increasing mean ALT activity over time. Lomustine dose reductions were necessary in 3 dogs, and discontinuation was required in 2.…”
Section: Discussionsupporting
confidence: 54%
“…Hepatotoxicity associated with lomustine chemotherapy was reported in a previous study by Kristal et al 23 Although none of the dogs in the present study developed definitive evidence of overt liver failure, there was a significant trend toward increasing mean ALT activity over time. Lomustine dose reductions were necessary in 3 dogs, and discontinuation was required in 2.…”
Section: Discussionsupporting
confidence: 54%
“…In the present study, the CCNU‐DTIC protocol was discontinued based on increases in ALT activity alone; only 3 of the 7 dogs had evidence of liver dysfunction (based on hyperbilirubinemia in 1 dog and increased postprandial bile acid concentrations in 2 dogs). Because definitions varied, direct comparisons between the incidence of liver toxicity in the study reported here and the frequency in the report by Kristal et al 30 cannot be made. However, the median number of CCNU doses and median total cumulative CCNU dose in dogs with suspected hepatic damage were lower than the values reported by Kristal et al 30 (2 doses, 80 mg/m 2 versus 4 doses, 350 mg/m 2 ).…”
Section: Discussionmentioning
confidence: 75%
“…Because definitions varied, direct comparisons between the incidence of liver toxicity in the study reported here and the frequency in the report by Kristal et al 30 cannot be made. However, the median number of CCNU doses and median total cumulative CCNU dose in dogs with suspected hepatic damage were lower than the values reported by Kristal et al 30 (2 doses, 80 mg/m 2 versus 4 doses, 350 mg/m 2 ). This observation might suggest an additive or synergistic toxicity when CCNU and DTIC are combined.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Most often they cause acute injury, but in some instances CH or cirrhosis are potential sequele. Strong evidence indicates that treatment with phenobarbital, primidone, phenytoin, and lomustine can result in CH . In the case of phenobarbital, toxicity may be direct or related to altered metabolism of other xenobiotics.…”
Section: Etiologymentioning
confidence: 99%